Relation between Chronic Urticaria and Quality of Life: An Observational Study of 112 Portuguese Patients - Ana Rita Almeida; Bárbara Oliveiros; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Introduction: Chronic urticaria is a complex multifactorial dermatological disease. It is highly prevalent throughout the world and contributes to lower patients' quality of life. The purpose of this study is to evaluate the impact of chronic urticaria on the quality of life (QoL) and mental status in Portuguese patients. Methods: This observational study included the evaluation of Portuguese patients from the consultation of chronic urticaria in the Coimbra University Hospital Centre, using several questionnaires including: weekly urticaria activity score (UAS7), Urticaria Control Test (UCT), Dermatology Life Quality Index (DLQI), Chronic Urticaria Quality of Life Questionnaire (CU-Q2oL) and the Hospital Anxiety and Depression Scale (HADS). The results of the questionnaires were posteriorly analysed, and the quality of life and mental status assessed in these patients were correlated with sociodemographic parameters and clinical aspects of chronic urticaria. Results: We studied 112 patients, mainly female (80%), with an average age of 46 years, mostly classified with mild urticaria activity, according to UAS7, and the majority (85%) were poorly controlled, regarding the UCT classification. Using both CU-Q2oL and DLQI we obtained mean values of 48.98 (±19.53) and 7.23 (±7.67), respectively, that show a high impact on the QoL. CU also interferes with mental status values in HADS concordant with anxiety (in a total of 45 patients) and depression (in 22 patients). A strong and positive correlation was found between both instruments used to measure quality of life, with pruritus, number of papules, quality of sleep and the embarrassment caused by cutaneous lesions as the mostly affected parameters in our sample. QoL varies significantly with gender, degree of instruction, clinical severity of symptoms and level of disease control. Although not always directly related, clinical activity of the disease remains the most significant factor of patients' QoL. Anxiety and depression show a significantly relationship with quality of life, however it was not found a significant correlation with the urticaria clinical activity. Discussion: Patient-Reported Outcomes (PRO) proved to be a practical and effective tool in daily clinic assessment of Portuguese patients suffering from chronic urticaria. The variation of quality of life according to sociodemographic characteristics is in conformity with literature. Moreover, new results were achieved regarding the level of instruction. The mostly impaired domains in our sample's QoL are not totally identical to previous studies, which suggests a meaningful effect of the geographic location. This investigation supported the significant influence of clinical activity of the urticaria and psychological well-being in QoL as previously published. Conclusion: In Portuguese patients with chronic urticaria, it is essential to establish an integrated approach that encompasses the clinical control of urticaria, but also the control of the associated psychological symptomatology.